Penerapan Metode Fuzzy Tsukamoto untuk Mengidentifikasi Banjir Berdasarkan Curah Hujan dan Suhu di Kota Balikpapan pada Tahun 2015 sampai 2019 - Ria Adha Sulistyowati; Nashrul Millah (SPECTA Journal of Technology, 2021)
Flooding occurred in several areas in Balikpapan is still a big issue. Floods that occurred in several places in Balikpapan were basically caused by the unavailability of trenches and places to drain rainwater. This causes rainwater going straight down the road and creating a puddle. One way to anticipate the occurrence of floods is to know the conditions that trigger floods, which are rainfall and air temperature. For this reason, it is a necessary to create a classification system for the level of rainfall and air temperature that affect flooding. The method that can be used for this problem is fuzzy logic, specifically the Tsukamoto method. Tsukamoto method of fuzzy logic is one of the most frequently used methods for prediction. Therefore, method can be used to identify floods. Input variables used in this study are rainfall and temperature, while the output variable is flood or not flood.